القواعد والضوابط لتفسير الكلمات القرآنية - Yasir, Muhammad (TAFAKKUR : Jurnal Ilmu Al-Qur'an dan Tafsir, 2020)
There are the greats correlations between the words of the Qur'an and understanding of the verse. It is the first gate before understanding a verse, where the right understanding of a verse depends on the initial understanding of a word. The conclusion from this study shows how important it is to understand the Qur'anic words correctly and intact. This must be based on the rules and dhowabit, especially the rules which mentioned by previous scholars and some of the new rules that we need today. A mufassir or mutadabbir (a person who recites Al-Qur’an) will not understand the purpose or sign of a quranic verses perfectly except by understanding the word in that verses as a whole. The rules and dhowabit (conditions) that resulted from this study amounted to 14 rules and 2 dhowabit that specifically functioned to understand the words of the Qur'an not mentioned before. This research is qualitative that uses the descriptive analysis to the library sources, which is related to the words (sentences) of the Qur'an, both the lexical side and its position (maudhi`) in the sentence. And this research too compares each opinion with similar interpretations, so that a special rule and dhobit is formed in understanding the Qur'anic words properly and appropriately. هناك علاقة وثيقة وقوية بين الكلمات وتفسير الآية، فهو كالبوابة الأولى قبل دخول في الآية، حيث جاء الخطأ والصواب في تفسير الآية توقف على تفسير الكلمة بدايةً. يتخلص هذا البحث في بيان مدى أهمية تفسير الكلمة القرآنية بشكل صحيح كامل. وذلك باعتماد على القواعد والضوابط، وهي القواعد والضوابط التي ذكرها العلماء السابقون وبعض القواعد الجديدة التي يتطلب منا وجودها اليوم. هذا، لأن المفسر أو المتدبر كلام الله تعالى لن يصل إلى معاني الآيات أو إشارات الآية القرآنية بشكل صحيح كامل إلا بفهم كلمات الآية مثل ما فهمه العرب القدماء. تحصّل الباحث في هذه الدراسة على أربع عشرة قاعدة وضابطين وهي لم تكن مذكروة من قبل. وأما المنهج الذي يستخدم في هذا البحث فهو منهج نوعي تحليلي تقعيدي معتمدا على المصادر والمراجع التي تتعلق بكلمة القرآن في دلالة ألفاظها، من جانبها المعجمي (leksikal) وموضعها في الجملة (grametikal) مع مقارنة الأراء المعروضة بآراء اللغويين، لما يحصل خلاف في تحديد تفسير الكلمة بين المفسرين. وبالتالي تشكلت القواعد والضوابط الخاصتان لفهم معنى كلمة القرآن بشكل صحيح كامل.